So far and yet so close: The new Quechua activisms facing the Peruvian State - Zavala, Virginia; Andrade Ciudad, Luis (Boletín de Filología, 2023)
In a Latin American historical context in which the State opens opportunities for the promotion of diversity while depoliticizing the identity of indigenous peoples and the struggle for their rights, some Peruvian collectives are developing novel and creative initiatives in favor of Quechua, deploying linguistic agency and activism in close connection with other citizen concerns. Some of these groups, made up mainly of young people, choose to act outside the state, rejecting state language policies outright, while others take advantage of the funding options and symbolic recognition that officialdom offers them. Based on the review of two cases that we consider representative of both positions, the Quechua for All project and the Puriyninchik Association, we propose that the relationship with the State constitutes a relevant axis for observing Latin American language activism, and we examine the challenges and possibilities faced by the collectives as they move along these paths.